Delivery of liothyronine by microneedle patch for the treatment of hypothyroidism - Yasmine Gomaa; Tasnuba Hasin; Martin N. Griffin; Thy C. Nguyen; Richard K. Noel; Laura O’Farrell; Elizabeth A. McAninch; Ann Marie Kaiser; Levi B. Wood; Mark R. Prausnitz (Drug Delivery and Translational Research, 2026)

Integrating soil monitoring and machine learning to map historical tillage and stubble management across Australian cropping systems (2001–2023) - Chiara Pasut; Ming Li; Bonnie Armour; Christina Asanopoulos; Glenn Brown; Doug Crawford; Mark Farrell; Mary Garrard; Frances Hoyle; Malcolm McCaskill; Massimiliano De Antoni Migliorati; Robert Moreton; et al. (Computers and Electronics in Agriculture, 2026)

Impact of wildfires on sediment quality in estuaries in New South Wales, Australia - Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Mark Farrell; Sally A. Bracewell; Emma L. Johnston (Chemosphere, 2025)

Isotopically resolved fate and processes of nitrogen in a constructed wetland treating domestic effluent - Danielle J. Allen; Mark Farrell; Wei Wen Wong; Jianyin Huang; Luke M. Mosley (Science of The Total Environment, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Microbial communities in biosolids-amended soils: A critical review of high-throughput sequencing approaches - Cameron J. Reid; Mark Farrell; Jason K. Kirby (Journal of Environmental Management, 2025)

Antimicrobial resistant Enterobacterales of clinical importance in mute swans - Aneta Kovarova; Graham Prole; Maeve Louise Farrell; Mark Maguire; Louise Catherine Murphy; Alexandra Chueiri; Louise O'Connor; Georgios Miliotis; Dearbháile Morris; Liam P. Burke (Science of The Total Environment, 2025)

Soil N 2 O emissions during dry fallow periods - Rémi Cardinael; Louise Barton; Marc Corbeels; Johan Six; David Rowlings; Armwell Shumba; Regis Chikowo; Mark Farrell (Global Change Biology, 2024)
Shang et al. (2024) recently suggested to include nitrous oxide (N 2 O) emissions during the fallow period to better estimate N 2 O emission factors (EFs). We however highlighted several pitfalls of the proposed adjusted EFs for croplands in the specific case of dry subhumid, semiarid, and arid regions with dry fallow periods, these regions covering about 47% of the Earth's terrestrial area.

Longitudinal carriage of antimicrobial resistant Enterobacterales in healthy individuals in Ireland - Assessing the impact of recreational water use on duration of carriage - Maeve Louise Farrell; Alexandra Chueiri; Mark Maguire; Aneta Kovářová; Georgios Miliotis; Louise O'Connor; Francesca McDonagh; Sinead Duane; Martin Cormican; Genevieve Devane; Alma Tuohy; Niall DeLappe; et al. (Science of The Total Environment, 2023)

Novel insight into ammonium, phosphate, and iron(II) dynamics in the sediment porewater of a constructed wetland under artificial aeration through the diffusive equilibrium in thin films technique - Danielle J. Allen; Jianyin Huang; Mark Farrell; Luke M. Mosley (Environmental Research, 2023)

A novel eDNA approach for rare species monitoring: Application of long-read shotgun sequencing to Lynx rufus soil pawprints - Samantha A. Koda; Mark McCauley; Jessica A. Farrell; Isabelle J. Duffy; Fiona G. Duffy; Sandra Loesgen; Jenny Whilde; David J. Duffy (Biological Conservation, 2023)

Assessing the impact of recreational water use on carriage of antimicrobial resistant organisms - Maeve Louise Farrell; Alexandra Chueiri; Louise O'Connor; Sinead Duane; Mark Maguire; Georgios Miliotis; Martin Cormican; Brigid Hooban; Anne Leonard; William H. Gaze; Genevieve Devane; Alma Tuohy; et al. (Science of The Total Environment, 2023)

Imidacloprid exposure is detectable in over one third of wild bird samples from diverse Texas ecoregions - Meredith J. Anderson; Alan Valdiviezo; Mark H. Conway; Christina Farrell; R. Keith Andringa; Amy Janik; Weihsueh A. Chiu; Ivan Rusyn; Sarah A. Hamer (Science of The Total Environment, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads - Danielle J. Allen; Mark Farrell; Jianyin Huang; Simon Plush; Luke M. Mosley (Journal of Environmental Management, 2023)

Evidence for three distinct climate change audience segments with varying belief-updating tendencies: implications for climate change communication - Matthew Andreotta; Fabio Boschetti; Simon Farrell; Cécile Paris; Iain Walker; Mark Hurlstone (Climatic Change, 2022)
Mounting evidence suggests members of the general public are not homogeneous in their receptivity to climate science information. Studies segmenting climate change views typically deploy a top-down approach, whereby concepts salient in scientific literature determine the number and nature of segments. In contrast, in two studies using Australian citizens, we used a bottom-up approach, in which segments were determined from perceptions of climate change concepts derived from citizen social media discourse. In Study 1, we identified three segments of the Australian public (Acceptors, Fencesitters, and Sceptics) and their psychological characteristics. We find segments differ in climate change concern and scepticism, mental models of climate, political ideology, and worldviews. In Study 2, we examined whether reception to scientific information differed across segments using a belief-updating task. Participants reported their beliefs concerning the causes of climate change, the likelihood climate change will have specific impacts, and the effectiveness of Australia’s mitigation policy. Next, participants were provided with the actual scientific estimates for each event and asked to provide new estimates. We find significant heterogeneity in the belief-updating tendencies of the three segments that can be understood with reference to their different psychological characteristics. Our results suggest tailored scientific communications informed by the psychological profiles of different segments may be more effective than a “one-size-fits-all” approach. Using our novel audience segmentation analysis, we provide some practical suggestions regarding how communication strategies can be improved by accounting for segments’ characteristics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Keystone Perennial Grassland Species Control Soil Nitrogen Flows - Mark Farrell; Suzanne M. Prober (Ecosystems, 2021)

Review of high dose vancomycin in the treatment of Clostridioides difficile infection - Mazen S. Bader; John Hawboldt; Cheryl Main; Dominik Mertz; Mark Loeb; Alison Farrell; Joanna Joyce (Infectious Diseases, 2020)

Plastic Ingestion in Post-hatchling Sea Turtles: Assessing a Major Threat in Florida Near Shore Waters - Catherine B. Eastman; Jessica A. Farrell; Liam Whitmore; Devon R. Rollinson Ramia; Rachel S. Thomas; Jenifer Prine; Scott F. Eastman; Todd Z. Osborne; Mark Q. Martindale; David J. Duffy (Frontiers in Marine Science, 2020)

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

Effects of plant functional group removal on structure and function of soil communities across contrasting ecosystems - Nicolas Fanin; Paul Kardol; Mark Farrell; Anne Kempel; Marcel Ciobanu; Marie‐Charlotte Nilsson; Michael J. Gundale; David A. Wardle (Ecology Letters, 2019)
Loss of plant diversity has an impact on ecosystems worldwide, but we lack a mechanistic understanding of how this loss may influence below‐ground biota and ecosystem functions across contrasting ecosystems in the long term. We used the longest running biodiversity manipulation experiment across contrasting ecosystems in existence to explore the below‐ground consequences of 19 years of plant functional group removals for each of 30 contrasting forested lake islands in northern Sweden. We found that, against expectations, the effects of plant removals on the communities of key groups of soil organisms (bacteria, fungi and nematodes), and organic matter quality and soil ecosystem functioning (decomposition and microbial activity) were relatively similar among islands that varied greatly in productivity and soil fertility. This highlights that, in contrast to what has been shown for plant productivity, plant biodiversity loss effects on below‐ground functions can be relatively insensitive to environmental context or variation among widely contrasting ecosystems.

Network analysis reveals that bacteria and fungi form modules that correlate independently with soil parameters - Alexandre B. de Menezes; Miranda T. Prendergast‐Miller; Alan E. Richardson; Peter Toscas; Mark Farrell; Lynne M. Macdonald; Geoff Baker; Tim Wark; Peter H. Thrall (Environmental Microbiology, 2015)
Summary Network and multivariate statistical analyses were performed to determine interactions between bacterial and fungal community terminal restriction length polymorphisms as well as soil properties in paired woodland and pasture sites. Canonical correspondence analysis ( CCA ) revealed that shifts in woodland community composition correlated with soil dissolved organic carbon, while changes in pasture community composition correlated with moisture, nitrogen and phosphorus. Weighted correlation network analysis detected two distinct microbial modules per land use. Bacterial and fungal ribotypes did not group separately, rather all modules comprised of both bacterial and fungal ribotypes. Woodland modules had a similar fungal : bacterial ribotype ratio, while in the pasture, one module was fungal dominated. There was no correspondence between pasture and woodland modules in their ribotype composition. The modules had different relationships to soil variables, and these contrasts were not detected without the use of network analysis. This study demonstrated that fungi and bacteria, components of the soil microbial communities usually treated as separate functional groups as in a CCA approach, were co‐correlated and formed distinct associations in these adjacent habitats. Understanding these distinct modular associations may shed more light on their niche space in the soil environment, and allow a more realistic description of soil microbial ecology and function.

Photoassimilated carbon allocation in a wheat plant-soil system as affected by soil fertility and land-use history - Saikat Chowdhury; Mark Farrell; Nanthi Bolan (Plant and Soil, 2014)

Plant growth responses to biochar addition: an Australian soils perspective - Lynne M. Macdonald; Mark Farrell; Lukas Van Zwieten; Evelyn S. Krull (Biology and Fertility of Soils, 2014)

Biochar and fertiliser applications influence phosphorus fractionation and wheat yield - Mark Farrell; Lynne M. Macdonald; Greg Butler; Ivan Chirino-Valle; Leo M. Condron (Biology and Fertility of Soils, 2014)

Oligopeptides Represent a Preferred Source of Organic N Uptake: A Global Phenomenon? - Mark Farrell; Paul W. Hill; John Farrar; Thomas H. DeLuca; Paula Roberts; Knut Kielland; Randy Dahlgren; Daniel V. Murphy; Phil J. Hobbs; Richard D. Bardgett; Davey L. Jones (Ecosystems, 2013)

The fine line between mutualism and parasitism: complex effects in a cleaning symbiosis demonstrated by multiple field experiments - Bryan L. Brown; Robert P. Creed; James Skelton; Mark A. Rollins; Kaitlin J. Farrell (Oecologia, 2012)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Meningeal Coccidioidomycosis Diagnosed by Real-Time Polymerase Chain Reaction Analysis of Cerebrospinal Fluid - Matthew J. Binnicker; Alina S. Popa; Jelena Catania; Maria Alexov; Geoffrey Tsaras; Farrell Lloyd; Nancy L. Wengenack; Mark J. Enzler (Mycopathologia, 2011)

Improved simulation of Australian climate and ENSO‐related rainfall variability in a global climate model with an interactive aerosol treatment - Leon D. Rotstayn; Mark A. Collier; Martin R. Dix; Yan Feng; Hal B. Gordon; Siobhan P. O'Farrell; Ian N. Smith; Jozef Syktus (International Journal of Climatology, 2010)
We assess the simulation of Australian mean climate and rainfall variability in a new version of the CSIRO coupled ocean–atmosphere global climate model (GCM). The new version, called Mark 3.6 (Mk3.6), differs from its recent predecessors (Mk3.0 and Mk3.5) by inclusion of an interactive aerosol scheme, which treats sulfate, dust, sea salt and carbonaceous aerosol. Other changes include an updated radiation scheme and a modified boundary‐layer treatment. Comparison of the mean summer and winter climate simulations in Mk3.6 with those in Mk3.0 and Mk3.5 shows several improvements in the new version, especially regarding winter rainfall and sea‐level pressure. The improved simulation of Australian mean seasonal climate is confirmed by calculation of a non‐dimensional skill score (the ‘ M ‐statistic’), using data from all four seasons. However, the most dramatic improvement occurs in the model's simulation of the leading modes of annual rainfall variability, which we assess using empirical orthogonal teleconnections (EOTs). Compared to its predecessors and several international GCMs, Mk3.6 is best able to capture the spatial pattern of the leading rainfall mode, which represents variability due to the El Niño Southern Oscillation (ENSO). Mk3.6 is also best able to capture the spatial pattern of the second rainfall mode, which corresponds to increased rainfall in the northwest, and decreased rainfall over eastern Australia. We propose a possible mechanism for the improved simulation of rainfall variability in terms of the role of interactive dust in Mk3.6. By further suppressing convection over eastern Australia during El Niño events, dust feedbacks may enhance rainfall variability there, in tune with the model's ENSO cycle. This suggests that an interactive aerosol treatment may be important in a GCM used for the study of Australian climate change and variability. Mechanistic sensitivity studies are needed to further evaluate this hypothesis. Copyright © 2009 Royal Meteorological Society

The effect of egg size and nutrient content on larval performance: implications to protracted spawning in northern pike (Esox lucius Linnaeus) - Brent A. Murry; John M. Farrell; Kimberly L. Schulz; Mark A. Teece (Hydrobiologia, 2008)

Behaviour and physiology of sockeye salmon homing through coastal waters to a natal river - Glenn T. Crossin; Scott G. Hinch; Steven J. Cooke; David W. Welch; Sonia D. Batten; David A. Patterson; Glen Van Der Kraak; J. Mark Shrimpton; Anthony P. Farrell (Marine Biology, 2007)

Settlement, early growth and survival of Haliotis rubra in response to different algal species - Sabine Daume; Anton Krsinich; Steve Farrell; Mark Gervis (Journal of Applied Phycology, 2000)